Draft Tenth Five Year Plan 2002-2007 Volume-II Government of Rajasthan - Planning Commission (Planning Commission, 2002)
Draft Tenth Plan 2002-07 and Annual Plan 2002-03 Proposed Outlay Draft Tenth Plan 2002-07 and Annual Plan 2002-03 Proposed Outlay Physical Targets & Achievements Draft Tenth Plan (2002-07) Proposals for Spilover and Ongoing Programmes/Projects Draft Tenth Plan (2002-07) Proposed for Maximising Benefits of Completed Programmes/Projects Draft Tenth Plan (2002-07) Proposals for Programmes/Projects - New Schemes Summary Statement Draft Tenth Plan (2002-07) proposals for Programmes/ProjectsStatement Regarding Externally Aided Projects Centrally Sponsored Schemes Draft Tenth Plan (2002-07) and Annual Plan 2002-03 Pradhan Mantri Gramodaya Yojana - Outlays/Expenditure.
Government of Rajasthan